Chromato-mass spectrometric characteristics of red clover and motherwort tinctures - V. M. Odyntsova; O. I. Panasenko; V. H. Korniievska; Yu. I. Korniievskyi; D. A. Didenko (Zaporozhye State Medical University, 2020)
Motherwort has a cardiotonic effect - slows the heart rate and increases the strength of heart contractions, antihypertensive - lowers blood pressure, has a calming and antispasmodic effect in disorders of the cardiovascular system: in the early stages of hypertensive heart disease, mild forms of angina pectoris, heart defects and Graves' disease. Red clover tincture is used for atherosclerosis, which is accompanied by headaches and tinnitus, but with normal blood pressure; it provides detoxification of the liver and the body as a whole by cleansing blood and lymph; improves bile flow; normalizes bowel activity. The purpose of the work is to determine, by means of gas chromatography, the component composition of red clover and motherwort tinctures. Materials and methods. Red clover grass (Trifolii pretense herba) was collected in Zakarpattia, Chynadiyovo village, in July 2019; motherwort grass (Leonuri herba) was collected on the experimental site of ZSMU in June 2019. The tinctures were prepared from fresh raw materials (1:5) by maceration, using 70 % ethanol as the extractant. The tinctures were examined using an Agilent 7890B gas chromatograph with a 5977B mass spectrometer detector. Results. 20 Components were identified with gas chromatography in red clover tincture, of which: 1 aldehyde, 2 ketones, 3 esters, 3 heterocyclic compounds, 3 acids, 4 alcohols, and 4 aliphatic carbohydrates. In the motherwort tincture 30 characteristic components were identified, related to: organic acids (3 compounds); ketones (4); esters (6); aliphatic carbohydrates (1); alcohols (2); heterocyclic compounds (2); glycosides (1); nitrogen-containing compounds (1); aromatic compounds (3); sesquiterpenoids (3); phenolic compounds (2); aldehydes (1); undetermined compounds (2). Conclusions. It was used a gas chromatograph with a mass spectrometric detector in this work. 30 components were identified in motherwort tincture, of which, considering the quantitative analysis of the total peak area and retention time, the following should be distinguished: RT 16.26 - n-hexadecanoic acid - 15.2 %; RT 17,695 - phytol - 13.66 %; RT 12,835 - ethyl-d-glucopyranoside -10.99 %; RT 6.451 - 4H-pyran-4-one, 2,3-dihydro-3,5-dihydroxy-6-methyl - 3.98 %; RT 20.7581 - penten-3-one, 1-(2,6,6-trimethyl-1-cyclohexen-1-yl) - 3.42 %; RT 10.43 - benzaldehyde, 2-hydroxy-6-methyl - 3.04 %; RT 3.664 -1,2-cyclopentanedione -1.22 %. In red clover tincture 20 components were identified, of which, considering the quantitative content, the following should be distinguished: RT 13.921 - myo-inositol, 4-C-methyl - 50.03 %; RT 12.742 - ethyl-d-glucopyranoside - 4.83 %; RT 22,435 - γ-sitosterol - 3.84 %; RT 16.261 - n-hexadecanoic acid - 3.72 %; RT 17,696 - phytol - 1.56 %; RT 8.764 - ethanone, 1- (2-hydroxy-5-methylphenyl) - 1.39 %. The two components coincide - n-hexadecanoic acid and phytol. In quantitative terms, there were more of them in the motherwort tincture. The results of the study can be used to develop the technology of herbal preparations, which include the raw material of red clover and motherwort. The study also has practical importance in the identification of raw materials that are included in the herbal products.